Effect of Polyphenols From Campomanesia adamantium on Platelet Aggregation and Inhibition of Cyclooxygenases: Molecular Docking and in Vitro Analysis - Lescano, Caroline H.; Freitas de Lima, Fernando; Mendes-Silvério, Camila B.; Justo, Alberto F. O.; da Silva Baldivia, Débora; Vieira, Cristiano P.; Sanjinez-Argandoña, Eliana J.; Cardoso, Claudia A. L.; Mónica, Fabíola Z.; Pires de Oliveira, Ivan (Frontiers in Pharmacology, 2018)
Campomanesia adamantium is a medicinal plant of the Brazilian Cerrado. Different parts of its fruits are used in popular medicine to treat gastrointestinal disorders, rheumatism, urinary tract infections and inflammations. Despite its widespread use by the local population, the mechanisms involving platelet aggregation and the inhibition of cyclooxygenase by C. adamantium are unknown. This study evaluated the chemical composition, antioxidant activities and potential benefits of the C. adamantium peel extract (CAPE) and its components in the platelet aggregation induced by arachidonic acid in platelet-rich plasma. Aspects of the pharmacological mechanism were investigated as follows: platelet viability, calcium mobilization, levels of the cyclic nucleotides cAMP and cGMP, thromboxane B2 levels, and the inhibitory effects on COX-1 and COX-2 were studied in vitro and using molecular docking in the catalytic domain of this protein. The major CAPE constituents standing out from the chemical analysis are the flavonoids, namely those of the flavones and chalcones class. The results showed that CAPE, quercetin and myricetin significantly decreased arachidonic acid-induced platelet aggregation; the assays showed that CAPE and quercetin decreased the mobilization of calcium and thromboxane B2 levels in platelets and increased cAMP and cGMP levels. Moreover, CAPE inhibited the activity of COX-1 and COX-2, highlighting that quercetin could potentially prevent the access of arachidonic acid more to the catalytic site of COX-1 than COX-2. These results highlight CAPE's potential as a promising therapeutic candidate for the prevention and treatment of diseases associated with platelet aggregation.